Literature Review Faktor Penyebab Stunting pada Balita di Nusa Tenggara Timur - Novia W.Y. Loni Ke; Scherly Hayer; Novita Moeda; Luh Putu Ruliati (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Stunting is a condition of growth failure in toddlers (infants under five years old) due to chronic malnutrition, resulting in the child being too short for their age. Malnutrition occurs from the time the baby is in the womb and in the early days after the baby is born, but stunting does not appear until the baby is 2 years old. This study aims to examine the factors associated with stunting in toddlers in East Nusa Tenggara. The method used in this study is a literature review study with specific studies from various scopes found to be combined and draw concise conclusions and obtained through the Google Scholar journal service provider with a custom range of 2015-2025. The results of the analysis show that there are factors associated with stunting in toddlers in East Nusa Tenggara, including infectious diseases, exclusive breastfeeding, low birth weight (LBW), birth length, immunization, parenting patterns, diet, sanitation, and economics.